Pengaruh Variabel Makro Terhadap Nilai Tukar Rupiah Atas Dolar AS Periode 2012-2015 - Yessica Tri Permatasari; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The aim of this research was to determine the influence of money supply, reward for Indonesian sharia Bank certificate (SBIS), import and export to the rupiah exchange rate on the US dollar during 2012-2015. The research methods used was quantitative method with multiple linear regression analysis. The data used in this study was secondary monthly time series data in time during 2012 - 2015. Data in this research were obtained from Central Bureau of Statistic (BPS) and Indonesian Economic and Financial Statistic (SEKI). The result of this study indicate that partially, the money supply and reward for SBIS has significant impact on the rupiah exchange rate on the US dollar during 2012-2015, while import and export has no significant effect on the rupiah exchange rate on the US dollar during 2012-2015. Simultaneously, money supply, SBIS return rate, import and export had significant effect to the rupiah exchange rate on the US dollar during 2012-2015.